2018
DOI: 10.1016/j.socscimed.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework

Abstract: Close-to-community (CTC) providers have been identified as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver. This study uses a two-stage exploratory approach drawing upon qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 76 publications
7
103
0
5
Order By: Relevance
“…Previous studies have shown that support and encouragement by family members and supervisors is an important motivating factor for CHWs [44], assisting them to gain con dence in interacting with men and in negotiating work-related challenges [46]. These ndings suggest a gender sensitization program is required not only for health facilities, but also for households that CHWs visit, and for household members of the CHWs themselves.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that support and encouragement by family members and supervisors is an important motivating factor for CHWs [44], assisting them to gain con dence in interacting with men and in negotiating work-related challenges [46]. These ndings suggest a gender sensitization program is required not only for health facilities, but also for households that CHWs visit, and for household members of the CHWs themselves.…”
Section: Discussionmentioning
confidence: 96%
“…The program appeared to have acceptability in the view of communities who were generally supportive of hiring community women as Anchal Maas and Assistants and were also ready to accept some changes in their access to resources and mobility in return for their good work. As most community health workers in rural health programs in LMICs are women, being cognisant of gender attitudes and roles ensures that these workers are supported and retained (9,44,45). Declarations…”
Section: Consentmentioning
confidence: 99%
“…Community-based health programs often employ women, engage a wide range of stakeholders, and build close relationships with communities, and are able to in uence gendered attitudes and norms relating to employment and mobility. These in turn affect health outcomes of individuals (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of differential data and analysis on how health programs impact gender-based factors, including of drowning prevention programs (12,13). Program effects on gender-based differences in mobility privileges, power relationships between community members and expectations on behaviour need to be measured to understand how they in uence these health outcomes (1,9). For example, previous research has shown that negative perceptions towards women's economic empowerment may lead to higher rates of domestic violence on working women (14), but if programs do not evaluate these outcomes, they will remain invisible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation